Biopolitični prispevek francoskih pravljic poznega 17. stoletja k oblikovanju disciplinarne družbe - Tratnik, Polona (Primerjalna književnost, 2022)
In the article, I address the formation of a disciplinary society, as re-flected in the aristocratic culture of French storytellers at the end of the seventeenth century. Fairy tales played an important role in what Norbert Elias called the civilizing process. In the case of fairy tales, this meant the formation of a polite court society as well as disciplining women. I explore the biopolitical aspects of fairy tales in those cir-cumstances, as it is at that time that fairy tales show social shifts and consolidation of certain concepts, especially a particular concept of femininity and a particular social role of women, which remain largely unchanged also later on. I analyze the tale of Cinderella as written by two different authors, Charles Perrault and Marie-Catherine d’Aulnoy. I compare them as regards the representation of gender, gender roles and relationships, as well as their messages and morals. In the second half of the twentieth century, thanks to Walt Disney’s adaptation of Perrault’s Cinderella, this version became the world’s most famous fairy tale about Cinderella. The biopolitical relevance of Perrault or Disney’s Cinderella as arguably the most globalized story in general has been and still is remarkable.
Keywords: 17. stol.; 17th cent.; aristocracy; aristokracija; Aulnoy, Marie-Catherine; biopolitics; biopolitika; Cinderella; civilizing process; court society; dvorska družba; fairy tales; francoska književnost; French literature; gender roles; Pepelka; Perrault, Charles; pravljice; proces civiliziranja; spolne vloge; women; ženske